Analisis Kesusahan Menuntaskan Pertanyaan Sub Bab Bilangan Cacah Sekolah Dasar - Unaenah, Een; Bakar, Muhammad Abu; Irmawati, Nabila (MASALIQ, 2023)
The purpose of this study is to learn why students have trouble working through questions about whole number operations. Descriptive qualitative research was used to conduct the study. Based on the results of daily tests that met the Minimum Completeness criteria (KKM), up to four third-grade students from SD Indonesia Smart, Tangerang City, were the participants in the study. Tests and interviews were used to collect data. Three story-based essai questions were included on the test instrument. According to the findings of the study, the following factors hinder students' ability to solve integer operations: 1) hardships in applying numerical activities; 2) hardships in getting it and making an interpretation of issues into numerical language; 3) troubles in taking care of issues connected with number tasks (expansion, deduction, expansion, and division). It tends to be seen from the consequences of the examination that the extent of understudies' trouble in performing number-crunching tasks comes to 60%.